2008
DOI: 10.1007/s10840-008-9270-x
|View full text |Cite
|
Sign up to set email alerts
|

Early heparinization decreases the incidence of left atrial thrombi detected by intracardiac echocardiography during radiofrequency ablation for atrial fibrillation

Abstract: Early administration of intravenous heparin, specifically before transseptal puncture, decreases the incidence of left atrial thrombi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 38 publications
2
53
1
1
Order By: Relevance
“…It has been observed that thrombi can form on the transseptal sheath and/or the electrode catheter almost immediately after crossing the septum and that early heparinization substantially decreases this risk. 768,802,803,804,846,847,848 A recent meta-analysis of more than 7000 patients supports this recommendation, showing that performing ablation of AF with a target ACT >300 seconds decreases the risk of thromboembolic complications without increasing the risk of bleeding. 849 Seventy-seven percent of the writing group members administer heparin prior to the transseptal puncture.…”
Section: Section 7: Technical Aspects Of Ablation To Maximize Safety mentioning
confidence: 96%
“…It has been observed that thrombi can form on the transseptal sheath and/or the electrode catheter almost immediately after crossing the septum and that early heparinization substantially decreases this risk. 768,802,803,804,846,847,848 A recent meta-analysis of more than 7000 patients supports this recommendation, showing that performing ablation of AF with a target ACT >300 seconds decreases the risk of thromboembolic complications without increasing the risk of bleeding. 849 Seventy-seven percent of the writing group members administer heparin prior to the transseptal puncture.…”
Section: Section 7: Technical Aspects Of Ablation To Maximize Safety mentioning
confidence: 96%
“…23 These data indicate that an activated clotting time of 300 to 400 seconds may be optimal for minimizing thrombembolic events, whereas there was no benefit from heparin and a glycoprotein IIb/IIIa inhibitor application compared to heparin alone. 44 The time point of heparin application also seems to be important because hemostatic activation 31 and thrombus formation 45 were significantly…”
Section: Periprocedural and Postprocedural Anticoagulation Managementmentioning
confidence: 99%
“…143,165 Early heparinization, the use of intracardiac ultrasonography, and aggressive anticoagulation regimens appear to have reduced the incidence of this complication. 180 Left Atrial-Esophageal Fistula. A potentially catastrophic consequence of AF ablation is the formation of a fistula between the posterior left atrium and the esophagus.…”
Section: Complicationsmentioning
confidence: 99%